Regulating pharmacists as contraception providers: A qualitative study from Coastal Kenya on injectable contraception provision to youth - Gonsalves, Lianne (PLoS One, 2019)
INTRODUCTION: Young people worldwide are often reticent to access family planning services from public health facilities: instead, they choose to get contraception from private, retail pharmacies. In Kenya, certain contraceptives are available in pharmacies: these include injectables, which can be dispensed but not administered, according national guidelines. However, Kenya struggles with enforcement of its pharmacy regulations and addressing illegal activity. Therefore, in this qualitative study, we assessed private pharmacies as an existing source of injectable contraception for young Kenyans (age 18–24), and investigated the perceived quality of service provision. METHODS: This study used: focus group discussions (6) with young community members; in-depth interviews (18) with youth who had purchased contraception from pharmacies; key informant interviews with pharmacy personnel and pharmacy stakeholders (25); and a mystery shopper (visiting 45 pharmacies). RESULTS: The study found that for injectable contraception, private pharmacies had expanded to service provision, and pharmacy personnel’s roles had transcended formal or informal training previously received–young people could both purchase and be injected in many pharmacies. Pharmacies were perceived to lack consistent quality or strong regulation, resulting in young clients, pharmacy personnel, and regulators being concerned about illegal activity. Participants’ suggestions to improve pharmacy service quality and regulation compliance focused on empowering consumers to demand quality service; strengthening regulatory mechanisms; expanding training opportunities to personnel in private pharmacies; and establishing a quality-based ‘brand’ for pharmacies. DISCUSSION: Kenya’s recent commitments to universal health coverage and interest in revising pharmacy policy provide an opportunity to improve pharmacy quality. Multi-pronged initiatives with both public and private partners are needed to improve pharmacy practice, update and enforce regulations, and educate the public. Additionally, the advent of self-administrable injectables present a new possible role for pharmacies, and could offer young clients a clean, discreet place to self-inject, with pharmacy personnel serving as educators and dispensers.